Robot Perahu Pengangkut Sampah Berbasis Pengolahan Citra - Ketut Abimanyu; Saeful Rohman; Asgia Setya; Pradito Octa (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2019)
This research explain about garbage carrier roboboat. the purpose of making this robot is to reduce the trash found on river surfaces. Indonesia is an archipelagic country, this country dominated by ocean as rives estuary, however many of the resources produced from the sea have been polluted due to dirty and full of garbage from the river. So with the creation of this robot, it is expected to minimize the pollution. The shape of this robot is a boat that can operate in rivers and waters that still allows this robot to operate. This robot uses a brushless motor to move on the surface of the water and electronic speed control to control the brusless motor speed with the PWM setting method, for the navigation system the HC5409 ultrasonic sensor is used to detect any obstacles that avoid collisions, then image processing techniques are applied to detect garbage on the surface of the water, The Matlab R2012a program is an application used to process this image processing technique. In sum, the working process of this boat robot is, first, the navigating robot looks for garbage objects by detecting it using image processing. If garbage is detected, the robot will maneuver and activate brushless motors with garbage manuever algorithms, instructions sent from the microcontroller to Arduino Mega 2560, the robot approaches garbage object and crawl it. There are two garbage objects determined, namely styrefoam and a blue bottle, this boat can execute advanced, right and left maneuvers with the percentage of success reaching 80-90%. The advantage of this boat is that garbage objects can be detected from various directions and operate semi-automatically . Keywords :MATLAB, Image processing ,Motor brushless, Arduino Mega 2560 , manuever .